2010
DOI: 10.1002/mds.22519
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary dysfunction in Parkinson's disease

Abstract: Bladder dysfunction (urinary urgency/frequency) and sexual dysfunction (erectile dysfunction) are common nonmotor disorders in Parkinson's disease (PD). In contrast to motor disorders, genitourinary autonomic dysfunctions are often nonresponsive to levodopa treatment. The brain pathology causing the bladder dysfunction (appearance of overactivity) involves an altered dopamine-basal ganglia circuit, which normally suppresses the micturition reflex. By contrast, hypothalamic dysfunction is mostly responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 120 publications
(171 reference statements)
1
75
0
2
Order By: Relevance
“…In these studies, there was no discrimination of different types of bladder changes. (2,3) "Urge Urinary Incontinence" was considered a specific diagnosis and, according to the publications on the subject, is related both to own Parkinson's disease due to overactivity of the detrusor muscle of the bladder, as other causes, such as idiopathic presentation seen in men and women aged over 65 years, due in part of latent cerebral ischemia. (3) The Nursing Diagnosis "Overflow urinary incontinence", identified in the survey reaffirmed the multiple causes of bladder symptoms in patients with Parkinson's.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In these studies, there was no discrimination of different types of bladder changes. (2,3) "Urge Urinary Incontinence" was considered a specific diagnosis and, according to the publications on the subject, is related both to own Parkinson's disease due to overactivity of the detrusor muscle of the bladder, as other causes, such as idiopathic presentation seen in men and women aged over 65 years, due in part of latent cerebral ischemia. (3) The Nursing Diagnosis "Overflow urinary incontinence", identified in the survey reaffirmed the multiple causes of bladder symptoms in patients with Parkinson's.…”
Section: Discussionmentioning
confidence: 99%
“…(2,3) "Urge Urinary Incontinence" was considered a specific diagnosis and, according to the publications on the subject, is related both to own Parkinson's disease due to overactivity of the detrusor muscle of the bladder, as other causes, such as idiopathic presentation seen in men and women aged over 65 years, due in part of latent cerebral ischemia. (3) The Nursing Diagnosis "Overflow urinary incontinence", identified in the survey reaffirmed the multiple causes of bladder symptoms in patients with Parkinson's. Overflow urinary incontinence, was associated to men with benign prostatic hyperplasia, which is a chronic, complex, progressive disease and which is related to lower urinary tract symptoms, in addition to affecting the quality of life of affected patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[101][102][103] These rates tend to be lower if MSA has been carefully eliminated from the study population, as LUTS are found in nearly all MSA patients. 104 The most widely accepted theory explaining LUTS pathogenesis in PD is that the loss of basal ganglia neurons disrupts normal inhibition of the micturation reflex (located in the pontine micturation center), mediated by D1 receptors.10 5 This loss of reflex inhibition leads to an unstable bladder, resulting in the urgency and frequency symptoms most often described by PD patients. This theory is supported by reports of improved LUTS after DBS of the subthalamic nucleus.…”
Section: Genito-urinary Systemmentioning
confidence: 99%